Al Ghazali’s educational theories and influences on islamic and western civilizations - Rahimah, Embong; Abdul Hakim, Abdullah; Nor Afizan, Che Omar; Siti Murdhiah, Salleh (2017)
The paper aims to examine the educational theories and influences of Al-Ghazali in the context of Muslim civilizations and worldwide. Al-Ghazali was the reformer of Islamic civilization. He advocated that Divine revelation as the ultimate source of knowledge and is essential to recognize the reality. Initially, Al-Ghazali divides knowledge into two parts namely dogmatic and non-dogmatic. According to him, the objective of education is utility. His utility theory consists of individual as well as social phenomena. He has suggested a golden principle that subjects should be taught in their order of utility and importance. While the goal of education is formation, construction and completion of manners so that man can distinguish between good and bad. For the principles of curriculum construction, he has advocated the inclusion of both academic and religious subjects. This study found that Al-Ghazali’s theories and influences give some significant implications on educational fields and philosophical foundations of both Western and Islamic scholasticism.